Isotope records from Turborotalia cerroazulensis and Turborotalia pomeroli near the middle/late Eocene boundary (North Adriatic Sea, Croatia) - Premec-Fucek, Vlasta; Pearson, Paul N. (Anuário do Instituto de Geociências, 2006)
Abstract